Exploring effective methodologies in ESL education and the challenges of teaching English in a multilingual world. - Abduvakhobova Nodirabegim Abdivakhid qizi; Teshaboyeva Nafisa Zubaydulla qizi (Zien Journals, 2024)
Each of these methodologies has its strengths and can be effective depending on the learners' needs, contexts, and goals. Many teachers adopt a blended approach, incorporating elements from multiple methodologies to create a dynamic and responsive learning environment. The key is to remain flexible and attuned to the needs of the students, fostering an engaging and supportive atmosphere for language acquisition
Keywords: ESL teaching strategies; education in Uzbekistan